The effects of propolis on antibody production by laying hens - Freitas, J. A.; Vanat, N.; Pinheiro, J. W.; Balarin, M. R. S.; Sforcin, J. M. [UNESP]; Venancio, E. J. (Poultry Science Assoc Inc, 2011)
Propolis is a honeybee product showing several biological properties that enhance the immune response, depending on the concentration and intake period. Because propolis possesses an immunomodulatory action on mammals, the objective of our study was to investigate the effects of propolis on the humoral immune response of laying hens by evaluating antibody production. Laying hens (ISA Brown) were divided into 5 groups with 7 birds each. Group 1 was a nonimmunized control, whereas birds in group 2 were immunized intravenously with SRBC, and those in groups 3, 4, and 5 were treated intraperitoneally with propolis (2, 10, and 50 mg/kg, respectively) on 3 consecutive days and then inoculated intravenously with SRBC. Hematological and serological analyses were carried out on d 0, 3, and 38. Natural and specific antibody levels were determined by hemagglutination with rabbit red blood cells and SRBC, respectively. Propolis-treated birds (50 mg/kg) showed a significant decline in heterophils and in the heterophil: lymphocyte ratio. After SRBC immunization, significant increases in levels of IgG were observed in groups 4 and 5. Furthermore, higher levels of natural antibodies were observed in propolis-treated laying hens. The administration of propolis to laying hens increased the production of IgG specific to SRBC and natural antibodies, and could be used to increase antigen-specific antibody responses to vaccines.
Keywords: antibody; humoral immune response; laying hen; propolis